Increasing the Brand Awareness of Petra Production House through Events - Yehezkiel Brandon Limina Lay; Henny Putri Saking Wijaya (Kata Kita: Journal of Language, Literature, and Teaching, 2026)
Petra Production House (PPH) is a newly rebranded student film organization within Petra Christian University (PCU). Its main problem is a lack of brand awareness among the broader student body, evidenced by poor event attendance. To validate this issue, the writer has conducted a survey targeting university students. The results confirmed low recognition of PPH, with over 50% unaware of the organization, and revealed preferences for casual, community-based film events. The implemented solution was a series of movie night events enhanced with interactive elements such as discussion boards and snacks. This strategy targeted PCU students interested in film and casual events, using Instagram, group chats, and peer promotion as channels. The effectiveness of this solution was measured through post-event surveys, showing an increase in brand recognition and high enjoyment. Attendance increased fourfold compared to prior events, and over 90% of attendees recommended future events. The benefits include improved visibility, deeper audience engagement, and stronger brand perception.